Complete versus incomplete cytoreduction in peritoneal carcinosis from gastric cancer, with consideration to PCI cut-off. Systematic review and meta-analysis. Issue 7 (July 2015) - Coccolini, F.; Catena, F.; Glehen, O.; Yonemura, Y.; Sugarbaker, P.H.; Piso, P.; Montori, G.; Ansaloni, L.
Abstract Introduction The completeness of cytoreduction has been considerated as fundamental in increasing the life expectancy in patients with peritoneal carcinosis (PC) in gastric cancer. However no defintive data about the real effect of complete cytoreduction (CC) have still been published. Moreover the PCI cut-off to attempt CC with a reasonable risk-benefit ratio still lacks. Material and methods A systematic review with meta-analysis of trials of complete vs incomplete cytoreduction in patients with peritoneal carcinosis from GC was performed. Results Nine trials have been included (748 patients: 417 with CC0-CC1 and 324 with CC2-CC3 cytoreduction). 1, 2, 3 and 5 years survival is favorable to CC0-CC1 (Risk Ratio: 2.41, 8.18, 8.66, and 7.96 respectively). CC0 vs. CC1 survival benefit at 1 and 3 years: RR 2.28 and 6.36 respectively, favoring CC0. 1, 2, 3 and 5 years survival changes significantly above and below a PCI of 12. Conclusions 1, 2, 3 and 5-year overall survival is increased by CC0-CC1 cytoreduction in patients with PC from gastric origin. Moreover CC0 increases the 1 and 3 years survival when compared to CC1 cytoreduction.